Inventory Mapping and Performance of Large Manufacturing Firms in Kenya: Moderating Role of Information Technology Integration - Wangai, Peter Mugo; Osoro, Anthony; Wachiuri, Elizabeth (International Journal of Supply Chain and Logistics, 2026)
Purpose: This study explored the relationship between inventory mapping and performance of Large Manufacturing Firms in Kenya. The study also analysed the moderating effects of information technology integration on relationship between inventory mapping and performance of Large Manufacturing Firms in Kenya. Methodology: The study adopted cross sectional research design. The target population was 1659 managers working in supply chain, production and finance departments in large manufacturing firms in Kenya based on the 14 sectors obtained from Kenya Association of Manufacturers. The study used stratified random sampling to select a sample of 322 managers from finance, production, and supply chain. Primary data was collected through use of questionnaires. 10% of the sample size was piloted to test for validity and reliability of the research instrument. Data collected was analysed using SPSS version 26. Descriptive and inferential statistics was used to analyse the data. The findings were presented in tables and figures. Findings: The study concluded that outbound logistics mapping positively and significantly influences performance of large manufacturing firms in Kenya. In addition, the study concluded that inventory mapping positively and significantly influences performance of large manufacturing firms in Kenya. Unique Contribution to Theory, Policy and Practice: This study contributes to Six Sigma theory by showing that logistics and inventory mapping, strengthened by information technology integration, are key drivers of performance in large manufacturing firms. It informs policy by highlighting the need to support technology-enabled supply chain practices, and guides practice by demonstrating how integrated mapping approaches can enhance efficiency and competitiveness in the manufacturing sector.